2021
DOI: 10.1186/s12859-021-04144-1
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of pipelines for mapping, variant calling and interval padding, for the analysis of NGS germline panels

Abstract: Background Next-generation sequencing (NGS) represents a significant advancement in clinical genetics. However, its use creates several technical, data interpretation and management challenges. It is essential to follow a consistent data analysis pipeline to achieve the highest possible accuracy and avoid false variant calls. Herein, we aimed to compare the performance of twenty-eight combinations of NGS data analysis pipeline compartments, including short-read mapping (BWA-MEM, Bowtie2, Stampy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 49 publications
(76 reference statements)
0
2
0
Order By: Relevance
“…A number of studies have evaluated the performance of variant analysis toolchains using short-read aligners as “black box” tools, without consideration of the effect of aligner runtime configuration and performance on downstream variant analysis (e.g. Chen et al 2019 , Hwang et al 2019 , Schilbert et al 2020 , Zhao et al 2020 , Zanti et al 2021 , Barbitoff et al 2022 , Betschart et al 2022 ). The inconsistent results among such studies imply that default parameter settings are not always optimal in every variant analysis toolchain.…”
Section: Performance Optimizationmentioning
confidence: 99%
“…A number of studies have evaluated the performance of variant analysis toolchains using short-read aligners as “black box” tools, without consideration of the effect of aligner runtime configuration and performance on downstream variant analysis (e.g. Chen et al 2019 , Hwang et al 2019 , Schilbert et al 2020 , Zhao et al 2020 , Zanti et al 2021 , Barbitoff et al 2022 , Betschart et al 2022 ). The inconsistent results among such studies imply that default parameter settings are not always optimal in every variant analysis toolchain.…”
Section: Performance Optimizationmentioning
confidence: 99%
“…Recent studies [16,17] have shown that BWA-MEM achieved better sensitivity and false positives rate for DNA sequencing data, making it the optimal choice for Onkopipe, which focuses on DNA sequencing with an average read length of more than 70bp, such as FFPE materials that usually have a length larger than 100bp. (Table 1)…”
Section: Raw Data Preprocessingmentioning
confidence: 99%
“…equally accurate on simulated data, but fail to achieve the accuracy of alignment-based methods for quantification of human RNA-seq [10]. Various short-read aligners have been tested and compared for many applications [11][12][13][14][15][16][17]. Aligners such as HiSat2 [18,19] and STAR [8,9] specialize in mapping RNA-seq to genome sequences, a task that requires virtual splicing of read sequences into exons and generation of alignments that skip over introns in the reference.…”
mentioning
confidence: 99%